Avoidance of phrasal verbs by brazilian students - Heck, Simone Regina Favero (My University, 2020)
This paper demonstrates how a difficult topic in English Foreing Language (EFL) acquisition can be easier to understand upon the right instruction. The objective is to understand why Brazilian students avoid using Phrasal Verbs and the reasons that can cause the avoidance. To achieve this goal, specific approaches were studied such as the syntactic, morphologic and cognitive aspects of Phrasal Verbs. These specific points are the best way to understand how they are used and can be utilized to any teacher of EFL. To Brazilian students to master the theme and develop fluency in English, it is necessary to go deeper in aspects of the English Language that do not exist in the Portuguese Language, such as the non-existence of Phrasal Verbs in Portuguese, as well as the difference between satellite framed language and verb framed language in Talmy (1999). To practice Phrasal Verbs in class, the specific methodologies related to the topic are important to overcome difficulties in learning. For example: the imagery concept by Rudzka-Ostyn (2003) can be combined with traditional course books that have a reduced approach. [resumo fornecido pelo autor]
Este artigo demonstra como um tópico que alguns consideram difícil na aquisição da segunda língua em inglês pode ser mais fácil de entender com as instruções corretas. O objetivo é entender o porquê de os estudantes brasileiros evitarem usar os Phrasal Verbs e as características que podem causar a evasão. Para atingir o objetivo, foram estudadas abordagens específicas, como as sintáticas, morfológicas e cognitivas dos Phrasal Verbs. Esses pontos específicos são a melhor maneira de entender como são usados e podem ser aproveitados por qualquer professor de English Foreing Learning (EFL). Para os estudantes English Foreing Learning (EFL) brasileiros dominarem o tema é preciso aprofundar aspectos da Língua Inglesa que não existem na Língua Portuguesa, como a inexistência de Phrasal Verbs na Língua Portuguesa, bem como as diferenças entre a linguagem de satélite e a linguagem de verbos de Talmy (1999). Para a prática de Phrasal Verbs em sala de aula, as metodologias específicas relacionadas ao tema são importantes para superar as dificuldades de aprendizagem, explorando o conceito de imagens de Rudzka-Ostyn (2003) e outros conceitos específicos a serem aplicados nas lições padrão de Phrasal Verb de livros tradicionais que têm uma abordagem reduzida para o entendimento completo do estudante brasileiro aprendendo inglês como língua estrangeira. [resumo fornecido pelo autor]
Keywords: Língua inglesa - Estudo e ensino - Falantes estrangeiros; Língua inglesa - Verbos